Hydrodynamic patterns of droplets impacting on the coated substrates - Nai, Ze Wei (2018)
The topic on the hydrodynamic behavior of a droplet impinging onto a heated surface has been an area of interest where many researchers have conducted numerous studies and research on it. Surface engineering had advanced with the help of modern technology and many surfaces of different properties were made possible. Modified surfaces could provide a vast amount of engineering solutions in the field of droplet impingement but there is a lack in study and research conducted on this topic, especially coupled with the boiling phase change. Therefore, a study on droplet impingement on coated and heated surface is conducted. This study aims to study the effect of the hydrodynamic behavior of droplet impinging onto a surface coated with nanoparticles and the surface subjected to heat. This report presents both experimental results and theoretical explanations on water droplet impinging onto a coated and heated surface. Four different modified heating surfaces applied in the experiments were hydrophilic, super-hydrophilic, super-hydrophobic and a hybrid patterned surfaces. A droplet of water impinged onto the heated, modified surface with temperatures ranging from room temperature which was 23°C to 310°C. The spreading factor of the droplets for all four surfaces were found to increase as the Weber number increases. While the heated surface is at low temperature for the case of the hydrophilic, super-hydrophilic and hybrid patterned surface, the droplets were found to undergo a common hydrodynamic behavior which starts from deposition, contact boiling, partial rebound, complete rebound and receding break up when at higher Weber number. For the super-hydrophobic surface, the droplet was found to have only a complete rebound and receding break up at high Weber number. The spreading factors for all four surfaces were compared and found to have a linear relationship with the Weber number. Some possible future work in this area would be extremely vast as there are still many possible areas of interests. Some possible changes include changing the experiment mediums such as the use of ethanol instead of water or the test surface material could be changed given the technology of the modern world.